IoT Based Weather Watch - S. S. Bhosale,; P. D. Dangat,; F. D. Shaikkh,; Prof. M. N. Shinde, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The development and advance in technology, many things are changes. The technology laid out to understand its importance like in urban areas, the electrical Line to In this project, an ESP8266 microcontroller is used to monitor and control flood levels, air temperature, and hazardous gas levels using various sensors. The system is connected to the Blynk platform for remote monitoring and control. The flood monitoring system utilizes an ultrasonic sensor to measure water levels. When the water level exceeds a certain threshold, an alert is triggered to warn people in the area. The air temperature is monitored using a DHT11 sensor, which provides real-time temperature readings. This data can be used for environmental monitoring or to provide alerts in case of extreme temperatures. For hazardous gas detection, an MQ6 sensor is used to detect gases such as LPG, propane, and butane. When the gas concentration exceeds a safe level, an alert is triggered to warn people and prevent accidents.
Keywords: ESP8266 Microcontroller; LPG; IoT; DHT11 sensor